An Updated Checklist of Freshwater Gastropods (Mollusca: Gastropoda) of Bosnia and Herzegovina, with Emphasis on Crenobiotic Species - Dejan Dmitrović; Ana Savić; Goran Šukalo; Vladimir Pešić (Diversity, 2023)
An updated checklist of freshwater gastropods of Bosnia and Herzegovina, including 144 species and subspecies from 59 genera and 17 families, is presented in this paper. Hydrobiidae is the most diverse family, representing ~50% of the species richness in the country. In total, ~38% of the recorded taxa are endemic. The highest number of species was recorded from underground waters and/or springs, followed by rivers and standing waters. This inventory includes 18 crenobiotic taxa, of which 9 are endemic to Bosnia and Herzegovina. The country is divided between the Dniester–Lower Danube and Dalmatia ecoregions. The Dalmatia ecoregion has the highest overall diversity, i.e., 82 species and subspecies. Three invasive species are recorded in Bosnia and Herzegovina. Our study reveals that most species still lack conservation assessments, and only five species are nationally protected.